2018
DOI: 10.20944/preprints201801.0266.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can Genetics Predict Sports Injury? The Association of the Genes GDF5, AMPD1, COL5A1 and IGF2 on Soccer Player Injury Occurrence

Abstract: Genetics plays an integral role in athletic performance and is increasingly becoming recognised as an important risk factor for injury. Ankle and knee injuries are the most common injuries sustained by soccer players. Often these injuries result in players missing training and matches, which can incur significant costs to clubs. This study aimed to identify genotypes associated with ankle and knee injuries in soccer players and how these impacted the number of matches played. 289 soccer players including 46 pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Adolescence is characterized by maturation, which evokes muscle-tendon unit growth resulting in a steep increase in strength and power performance on the one hand (34) and an increased risk of injury on the other (45,58). Both physical performance and non-contact injuries are multifactorial domains including many intrinsic and extrinsic factors, which should also include the genetic profile (38,46). However, the effect of genetics on muscle injury predictors and neuromuscular performance in adolescents is scarce in current research.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is characterized by maturation, which evokes muscle-tendon unit growth resulting in a steep increase in strength and power performance on the one hand (34) and an increased risk of injury on the other (45,58). Both physical performance and non-contact injuries are multifactorial domains including many intrinsic and extrinsic factors, which should also include the genetic profile (38,46). However, the effect of genetics on muscle injury predictors and neuromuscular performance in adolescents is scarce in current research.…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine monophosphate deaminase isoform 1 (AMPD1) c.34 C > T (rs17602729) is an important regulator of skeletal muscle energy metabolism during exercise and leads to some related metabolic muscle diseases in subjects with the TT genotype [8]. This genotype causes metabolic myopathy with exercise-induced muscle symptoms such as early fatigue, cramps, and/or myalgia, which are related to the risk of injury [9] especially in football [10]. In angiotensin-converting enzyme (ACE) I/D (rs4646994), the I allele is associated with the resistance phenotype and the D allele with speed and power phenotypes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Examining the relationship between genetic variants and sports injuries in male soccer players, the study found that TT and CT genotypes were associated with injury risk and low match scores for AMPD1 rs17602729. 26 In Lithuanian elite athletes, significant relationships were found in terms of total genotype score consisting of genetic markers and susceptibility to athletic performance, which were examined in endurance-strength mixed logistic regression models, in terms of gender, endurance and strength. For AMPD1 rs17602729, one of these genetic markers, TT genotype was detected in only two cases in the sample, and data indicating that it may be associated with power score were determined.…”
Section: Discussionmentioning
confidence: 99%